Electrochemical Synthesis of Organoselenium Compounds: A Graphical Review - Hasimujiang, Balati; Ruan, Zhixiong (SynOpen, 2023)
Electrochemical synthesis, due to its environmentally benign, sustainable, and practical nature, has become an appealing and powerful substitute for traditional methods for oxidizing and reducing organic compounds. Thus, numerous valuable changes have been established in the field of organic synthesis through the utilization of electrochemistry. Among these electrochemical transformations, the formation of C–Se bonds stands out as an exceptionally noteworthy reaction type. In this graphical review, we present a succinct summary of the progress in utilizing electrochemical strategies for synthesizing organoselenium compounds.
Keywords: electrochemistry; organoselenium compounds; selenylation; difunctionalization; cyclization; cross-coupling